Clot imaging characteristics predict first pass effect of aspiration—first approach to thrombectomy. Issue 2 (April 2022) - Waqas, Muhammad; Li, Weizhe; Patel, Tatsat R; Chin, Felix; Tutino, Vincent M; Dossani, Rimal H; Ren, Zeguang; Guerrero, Waldo R; Borlongan, Cesario V; Pressman, Elliot; Snyder, Kenneth; Davies, Jason M; et al.
Background: The value of clot imaging in patients with emergent large vessel occlusion (ELVO) treated with thrombectomy is unknown. Methods: We performed retrospective analysis of clot imaging (clot density, perviousness, length, diameter, distance to the internal carotid artery (ICA) terminus and angle of interaction (AOI) between clot and the aspiration catheter) of consecutive cases of middle cerebral artery (MCA) occlusion and its association with first pass effect (FPE, TICI 2c-3 after a first attempt). Results: Patients ( n = 90 total) with FPE had shorter clot length (9.9 ± 4.5 mm vs. 11.7 ± 4.6 mm, P = 0.07), shorter distance from ICA terminus (11.0 ± 7.1 mm vs. 14.7 ± 9.8 mm, P = 0.048), higher perviousness (39.39 ± 29.5 vs 25.43 ± 17.6, P = 0.006) and larger AOI (153.6 ± 17.6 vs 140.3 ± 23.5, P = 0.004) compared to no-FPE patients. In multivariate analysis, distance from ICA terminus to clot ≤13.5 mm (odds ratio (OR) 11.05, 95% confidence interval (CI) 2.65–46.15, P = 0.001), clot length ≤9.9 mm (OR 7.34; 95% CI 1.8–29.96, P = 0.005), perviousness ≥ 19.9 (OR 2.54, 95% CI 0.84–7.6, P = 0.09) and AOI ≥ 137°^ (OR 6.8, 95% CI 1.55–29.8, P = 0.011) were independent predictors of FPE. The optimal cut off derived using Youden's index was 6.5. The area under the curve of a score predictive of FPE success was 0.816 (0.728–0.904, P < 0.001). In a validation cohort ( n = 30), sensitivity, specificity, positive and negative predictive value of a score of 6–10 were 72.7%, 73.6%, 61.5% and 82.3%. Conclusions: Clot imaging predicts the likelihood of achieving FPE in patients with MCA ELVO treated with the aspiration-first approach.